Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s11214-010-9710-7
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale Bright Fronts in the Solar Corona: A Review of “EIT waves”

Abstract: "EIT waves" are large-scale coronal bright fronts (CBFs) that were first observed in 195Å images obtained using the Extreme-ultraviolet Imaging Telescope (EIT) onboard the Solar and Heliospheric Observatory (SOHO). Commonly called "EIT waves", CBFs typically appear as diffuse fronts that propagate pseudo-radially across the solar disk at velocities of 100-700 km s −1 with front widths of 50-100 Mm. As their speed is greater than the quiet coronal sound speed (c s ≤200 km s −1 ) and comparable to the local Alfv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 87 publications
1
70
0
1
Order By: Relevance
“…The main contenders are the MHD wave/shock model (see Sections 2.2 and 6.1) and different magnetic reconfiguration models (Sections 2.3 and 6.2), as well as various combinations of these scenarios (Section 6.3). For more reviews on the topic of large-scale coronal waves, see Warmuth (2007); Wills-Davey and Attrill (2009) ;Gallagher and Long (2011);Zhukov (2011);Warmuth (2011); Patsourakos and Vourlidas (2012); Liu and Ofman (2014). The recently discovered phenomena of small-scale EUV waves (Innes et al, 2009;…”
Section: Overviewmentioning
confidence: 99%
“…The main contenders are the MHD wave/shock model (see Sections 2.2 and 6.1) and different magnetic reconfiguration models (Sections 2.3 and 6.2), as well as various combinations of these scenarios (Section 6.3). For more reviews on the topic of large-scale coronal waves, see Warmuth (2007); Wills-Davey and Attrill (2009) ;Gallagher and Long (2011);Zhukov (2011);Warmuth (2011); Patsourakos and Vourlidas (2012); Liu and Ofman (2014). The recently discovered phenomena of small-scale EUV waves (Innes et al, 2009;…”
Section: Overviewmentioning
confidence: 99%
“…From observations with the Extreme Ultraviolet Imager (EUVI) on board STEREO-B, Veronig et al (2010) found that coronal waves are dome shaped with erupting CME loops inside the dome. The CW properties can be found tabulated in Gallagher & Long (2011).…”
Section: In Hα Observations Prop-mentioning
confidence: 99%
“…The interpretations include fast-mode waves (Wills-Davey & Thompson 1999;Warmuth et al 2001;Schmidt & Ofman 2010), slow-mode waves or solitons (Wills-Davey et al 2007), and non-waves related to a current shell (Delannée et al 2008) or successively reconnecting mag- netic field lines at a CME front (Delannée et al 2014;Attrill 2010, and the references therein). More details on the properties and modelling of coronal waves can be found in several reviews by Vršnak & Cliver (2008), Long (2011), andVourlidas (2012). The most recent review by Liu & Ofman (2014) summarises the very latest findings from AIA/SDO observations and modelling of coronal/EIT waves.…”
Section: In Hα Observations Prop-mentioning
confidence: 99%
“…It should be noted at this point that the name "EIT wave" is typically used for historical reasons. To reflect the uncertainty surrounding the physical interpretation of "EIT waves" we shall adopt the suggested nomenclature of Gallagher & Long (2010) and refer to these disturbances as coronal bright fronts (CBFs) throughout this paper.…”
Section: Introductionmentioning
confidence: 99%
“…A conclusive result has been hampered by the diffuse nature of CBFs and the relatively low temporal cadence of the observing instruments, both of which make it difficult to characterize their true nature. A full review of CBFs, their morphology, kinematics, relationship to other solar phenomena, and theoretical interpretations may be found in Wills-Davey & Attrill (2010) and Gallagher & Long (2010).…”
Section: Introductionmentioning
confidence: 99%